Methods used for parasuicide: results of the WHO/EURO Multicentre Study on Parasuicide. - Michel, K; Ballinari, P; Bille-Brahe, U; Bjerke, T; Crepet, P; De Leo, D; Haring, C; Hawton, K; Kerkhof, A; Lönnqvist, J; Querejeta, I; Salander-Renberg, E; et al. (2000)
BACKGROUND: National suicide statistics show remarkable differences in the frequencies of various methods used for completed suicide. The WHO/EURO Multicentre Study on Parasuicide makes possible for the first time an international comparison of the frequencies of methods used in attempted suicide, because the data are based on geographical catchment areas of medical institutions. METHOD: Ongoing standardized monitoring of attempted suicide in all medical institutions serving the catchment areas was performed in 14 centres in 12 European countries. The data analysis is based on 20,649 events involving 15,530 persons, recorded between 1989 and 1993. RESULTS: The comparison of rates per 100,000 shows striking differences between the centres. The highest rates for drug overdoses were found for female attempters in Oxford (347/100,000), Helsinki (238/100,000) and Stockholm (221/100,000). Guipuzcoa had the lowest rates (61/100,000). The differences were most prominent in the age group 15-24, with outstanding rates for women in Oxford (653/100,000), which was mainly due to the frequent use of analgesics. Szeged had outstandingly high rates for pesticides and solvents. In some centres the use of multiple methods was frequent. CONCLUSIONS: There is a need, especially for areas with high frequencies for certain methods, to understand the factors involved and to develop new and specific prevention projects and to monitor their effects. The WHO/EURO Multicentre Study on Parasuicide has proved to be a useful and reliable instrument for continuous monitoring of trends in parasuicide.